2016
DOI: 10.1007/s00464-016-5001-z
|View full text |Cite
|
Sign up to set email alerts
|

Does surgeon volume matter in the outcome of endoscopic inguinal hernia repair?

Abstract: IntroductionFor open and endoscopic inguinal hernia surgery, it has been demonstrated that low-volume surgeons with fewer than 25 and 30 procedures, respectively, per year are associated with significantly more recurrences than high-volume surgeons with 25 and 30 or more procedures, respectively, per year. This paper now explores the relationship between the caseload and the outcome based on the data from the Herniamed Registry.Patients and methodsThe prospective data of patients in the Herniamed Registry were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 16 publications
1
26
0
3
Order By: Relevance
“…In addition to the hernia-and patient-related influencing factors on the outcome of inguinal hernia surgery, those related to the surgeon volume and hospital volume are also being increasingly investigated [8][9][10][11][12][13][14]. For example, one analysis of data from the Danish Hernia Database revealed that hospitals with less than 50 inguinal hernia repairs per year were found to have a significantly higher rate of recurrence operations (9.97% vs 6.06%; p < 0.0001) compared with hospitals with 50 and more operations [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the hernia-and patient-related influencing factors on the outcome of inguinal hernia surgery, those related to the surgeon volume and hospital volume are also being increasingly investigated [8][9][10][11][12][13][14]. For example, one analysis of data from the Danish Hernia Database revealed that hospitals with less than 50 inguinal hernia repairs per year were found to have a significantly higher rate of recurrence operations (9.97% vs 6.06%; p < 0.0001) compared with hospitals with 50 and more operations [9].…”
Section: Introductionmentioning
confidence: 99%
“…All the other aforementioned studies [8,[10][11][12][13] focused on the specific volume of an individual surgeon and its corresponding impact on the outcome. These studies have demonstrated that, as regards the surgeon volume, surgeons with higher caseloads have a lower recurrence rate [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The learning curve for endoscopic techniques is estimated to be 50–100 cases, with the first 30–50 being the most critical, whereas the Lichtenstein technique is easier to teach and replicate at all levels. The outcomes of non‐experts and supervised residents performing the Lichtenstein repair for primary inguinal hernias are comparable to those of experts . For example, in our experience during the humanitarian mission, organized by Hernia Reapir For Underserved (HRFU), we adopted a validated competency‐based training program using the Operative Performance Rating Scale; after 364 procedures, 81 local surgeons successfully completed the program, and the overall operative complication rate during training series was 1.1% .…”
Section: Open Versus Laparoscopic Techniquesmentioning
confidence: 97%
“…Recurrence is a key outcome in hernia surgery, and usually requires re-operation. Such re-operations are also associated with worse outcomes than primary repair [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…There are few longitudinal studies comparing the need for surgery for recurrence between the two techniques and those that are available utilized data that are now historical [16,28]. Longitudinal assessments require careful consideration of competing risks.…”
Section: Introductionmentioning
confidence: 99%